2008
DOI: 10.1002/biof.5520320129
|View full text |Cite
|
Sign up to set email alerts
|

Aging skin is functionally anaerobic: Importance of coenzyme Q10 for anti aging skin care

Abstract: The functional loss of mitochondria represents an inherent part in modern theories trying to explain the cutaneous aging process. The present study shows significant age-dependent differences in mitochondrial function of keratinocytes isolated from skin biopsies of young and old donors. Our data let us postulate that energy metabolism shifts to a predominantly non-mitochondrial pathway and is therefore functionally anaerobic with advancing age. CoQ10 positively influences the age-affected cellular metabolism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 30 publications
2
59
2
5
Order By: Relevance
“…Concerning 6-phosphofructokinase, platelet type (ATP-PFK) which is upregulated with aging in our study, this enzyme catalyzes the phosphorylation of D-fructose 6-phosphate to fructose 1,6-bisphosphate by ATP, the first committing step of glycolysis. It has been shown that human primary keratinocytes derived from elderly donors showed higher glucose uptake and increased lactate production, which are the indicators of a shift in metabolism towards increased glycolysis [45]. Thus, the observed upregulation of ATP-PFK is correlated with the increased glycolysis in primary keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning 6-phosphofructokinase, platelet type (ATP-PFK) which is upregulated with aging in our study, this enzyme catalyzes the phosphorylation of D-fructose 6-phosphate to fructose 1,6-bisphosphate by ATP, the first committing step of glycolysis. It has been shown that human primary keratinocytes derived from elderly donors showed higher glucose uptake and increased lactate production, which are the indicators of a shift in metabolism towards increased glycolysis [45]. Thus, the observed upregulation of ATP-PFK is correlated with the increased glycolysis in primary keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these can either be synthesized or extracted and subsequently purified and then sold (de Magalhães, 2013). The most common antioxidants include vitamins A, C and E, as well as the coenzyme Q 10 , the latter extensively advertised in face creams (Prahl et al, 2008), but also found to be effective in preserving mitochondrial respiratory function in aged rat skeletal (Sugiyama et al, 1995) and cardiac muscles (Park and Prolla, 2005). However, some studies have revealed that antioxidants do not delay the aging process per se, but rather contribute to increase longevity (Holloszy, 1998).…”
Section: Aging Therapies—cure Aging or Die Trying?mentioning
confidence: 99%
“…Derinin yaşlanması zamana bağımlılığına göre incelendiğinde iki gruba ayırılabilir 10,[18][19][20][21] . a) İntrinsik Yaşlanma (zamana bağlı olarak doğal yaşlanma): Kronolojik ve genetik nedenlerle, hücre yenilenmesinin yavaşlamasıyla başlayan ve durmasıyla devam eden dönemdir.…”
Section: Ci̇lt Yaşlanmasiunclassified
“…Hem intrinsik hem de ekstrinsik yaşlanma nedeni ile cilt nemini kaybederek kurur, bununla birlikte ileri yaşlarda hormonal nedenler ile deride bağ dokusu proteinleri azalır 10,[18][19][20] . İntrinsik yaşlanmanın belirtileri arasında; ince ve transparan bir cilt görünüşü, ince çizgiler, subkütan tabakadaki yağ hücrelerinin azalmasıyla göz çukuru ve yanaklarda çökme, kuru cilt, deri kalınlığında artış nedeniyle UV ışınlarına karşı eritematöz tepkide azalma, pigmentasyona bağlı yaşlılık çilleri, melanosit miktarının azalmasıyla deride beyazlaşma, derinin mikro sirkülasyonunda ve esnekliğinde azalma yer alır 18,20,21 . Ekstrinsik yaşlanmada ise, uzun süreli güneş ışınlarına maruziyet UVA ve özellikle UVB ışınlarına bağlı foto yaşlanma meydana gelir 1 .…”
Section: Ci̇lt Yaşlanmasiunclassified
See 1 more Smart Citation